A three-dimensional manganese model for the management of a monomictic drinking water reservoir. (December 2021) - Zhang, Fuxin; Zhang, Hong; Bertone, Edoardo; Stewart, Rodney; Shen, Xia; Cinque, Kathy
Abstract: A comprehensive spatial and temporal understanding of the manganese cycle in drinking water reservoirs has beneficial implications for the management of water treatment related issues. In this study, a three-dimensional manganese cycle model was developed and coupled with a hydrodynamic model, for the simulation of the distribution of manganese in a monomictic water reservoir. The model was successfully validated and used to model and predict the spatial-temporal manganese variation in the reservoir. Results showed that the variations of the thermal structure of the reservoir affect the seasonal change of manganese levels and in turn the peak concentrations of manganese in the epilimnion. It was also evident that the high level of dissolved oxygen in the epilimnion promotes the oxidation of soluble manganese, and the oxidised particulate Mn settles rapidly. The advection processes mainly caused by wind-driven currents play a vital role in rising or decreasing the level of soluble manganese near the dam wall. The developed numerical tool allows the user to gain a better understanding of spatial manganese distribution in different locations and depths of the reservoir under different wind/rain conditions, among others; such knowledge empowers the local water utility and enables more targeted, optimized water treatment strategies. Highlights: A three-dimensional manganese cycle model was developed and validated. Thermal structure of a monomictic reservoirs affects the peak of manganese significantly. The increase of DO in the epilimnion contributes to the oxidation process of soluble Mn. Wind driving currents dominate the horizontal transport of manganese.